miR-532 promotes colorectal cancer invasion and metastasis by targeting NKD1 - Song, Xujun; Wu, Rong; Tao, Qingsong; Zhao, Liangtao; Ji, Zhenling (Cellular and Molecular Biology, 2019)
The aim of this study was to investigate the effect of microRNA-532 (miR-532) on invasion and metastasis of colorectal cancer (CRC) cells, and the underlying mechanism. Human CRC cell line (HCT116) and normal colon (FHC) cells were used for this study. The cells were transfected with naked cuticle homolog 1 (NKD1) overexpression plasmid, miR-532 mimics, miR-532 inhibitor or miR-532 non-homologous sequence using lipofectamine 2000. Real-time quantitative polymerase chain reaction (qRT-PCR) was used to determine the expression of miR-532 in CRC cells, and a combination of scratch and Transwell assays was used to assess the effect of miR-532 on migration and invasion of CRC cells. Western blotting was used to determine the effect of miR-532 on NKD1 expression in CRC cells. Bioinformatics analysis and luciferase reporter gene assay were used to assess the regulatory effect of miR-532 on NKD1. The expression of miR-532 was upregulated in CRC cells relative to normal colon cells (p < 0.05). The HCT116 cells transfected with miR-532 mimics migrated faster than those of miR-532 negative control (miR532-NC) group (p < 0.05). The migration ability of HCT116 cells transfected with miR-532 inhibitor was significantly reduced, when compared with that of miR532-NC group (p < 0.05). The invasive ability of HCT116 cells transfected with miR-532 mimics was significantly higher than that of miR532-NC cells (p < 0.05). However, inhibition of miR-532 expression significantly reduced the invasive ability of HCT116 cells (p < 0.05). Results of bioinformatics showed that miR-532 had specific binding sequence with the 3'UTR region of NKD1. After cloning the sequence into the luciferase reporter plasmid, miR-532 significantly inhibited the expression of NKD1 (p < 0.05). However, miR-532 had no inhibitory effect on mutated NKD1 3'UTR (p > 0.05). Results of Western blotting showed that increased miR-532 expression significantly reduced the expression of NKD1, while decreased miR-532 expression promoted the expression of NKD1 (p < 0.05). Overexpression of NKD1 significantly down-regulated miR-532 overexpression and promoted CRC cell invasion and metastasis (p < 0.05). miR-532 is highly expressed in CRC cells and directly inhibits NKD1 expression, while enhancing invasion and metastasis of CRC cells. It promotes the development of CRC by inhibiting the expression of NKD1.